Effects of Distortion on Wire and Arc Additive Manufacturing Straight Walls - Adebayo, A; Stephen, J.T (Journal of Building Construction, Planning and Materials Research, 2017)
Wire and Arc Additive Manufacturing (WAAM) is a developing rapid prototyping and manufacturing technology which allows the production of large custom made metal parts with high deposition rates, a major concern of the aircraft industry. Despite this, there is few researches on the design method and application of WAAM technology in the aircraft industry. The overall aim of this paper is to study the machinability of the part manufactured through is process especially when a base plate is require. The results showed that removing the best plate prior or after machining can have a significant effect on the overall effective wall width of the samples.